Design and development of multimedia and multi-marker detection techniques in interactive augmented reality colouring book - Lee, Angeline Ling Sing; Awang Asri Awang Ibrahim; Ng, Giap Weng; Muzaffar Hamzah; Wong, Chun Yung (2020)
The aim of this paper is to the design and develop multimedia and multi-markers detection techniques in interactive Augmented Reality (AR) colouring book application for aquarium museum. This study is conducted to create entertaining AR colouring mobile application on Android Operating System which allows users to express, create and interact with their creativity through colouring activities. It allows users to engage and relish the stimulating colouring book content by switching between a reality and augmented world. Conversely, users may tend to lose interest in the colouring activities, but with AR technology it keeps colouring relaxing and inspiring. The design and development of this project was carried out using Unity3D integrates with Vuforia Engine. The multimedia and multi-markers scripting was written in C# programming language.